2016
DOI: 10.1093/glycob/cww039
|View full text |Cite
|
Sign up to set email alerts
|

α2–6 sialylation is a marker of the differentiation potential of human mesenchymal stem cells

Abstract: Human somatic stem cells such as human mesenchymal stem cells (hMSCs) are considered attractive cell sources for stem cell-based therapy. However, quality control issues have been raised concerning their safety and efficacy. Here we used lectin microarray technology to identify cell surface glycans as markers of the differentiation potential of stem cells. We found that α2-6Sia-specific lectins show stronger binding to early passage adipose-derived hMSCs (with differentiation ability) than late passage cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Recent reports using lectin microarrays have demonstrated changes in sialylation of glycoproteins during senescence in human mesenchymal stem cells and human skin fibroblasts [13, 28]. Here, we show that sialylation of glycoproteins in human skin fibroblasts was decreased during the process to senescence via increased sialidase NEU1 expression.…”
Section: Discussionsupporting
confidence: 56%
“…Recent reports using lectin microarrays have demonstrated changes in sialylation of glycoproteins during senescence in human mesenchymal stem cells and human skin fibroblasts [13, 28]. Here, we show that sialylation of glycoproteins in human skin fibroblasts was decreased during the process to senescence via increased sialidase NEU1 expression.…”
Section: Discussionsupporting
confidence: 56%
“…Tateno et al. combined lectin microarray technology with flow cytometry analysis and anion‐exchange chromatography and found that α2‐6Sia‐specific lectins showed higher binding affinity for human mesenchymal stem cells (hMSCs) with differentiation potential, suggesting that α2‐6Sia.α2‐6sialylation of integrinα5 could function as a marker for differentiation potency of stem cells including adipose‐derived hMSCs, bone marrow‐derived hMSCs, and cartilage tissue‐derived chondrocytes . A lectin microarray showed increased GlcNAc protein modification and α‐1‐2‐fucosylation but decreased α‐1‐6‐fucosylation, α‐2‐6‐sialylation, and α‐1‐6‐mannosylation during ESC adipogenesis …”
Section: Application Of Lectin Microarrays For Biomarker Discoverymentioning
confidence: 99%
“…Adipose tissue, bone marrow, and umbilical cord blood are harvested sources of MSCs (71,72). MSCs are considered very valuable cell sources for stem cell-based therapy because of the probability of teratoma formation in ESCs and iPSCS (73,74). The ability to adhere to plastic surfaces is one of the main characteristics of MSCs and it is also useful for glycoengineering studies (71).…”
Section: Mesenchymal Stem Cell Sialylated N-glycansmentioning
confidence: 99%
“…Comparisons of lectin binding intensity of early (with differentiation ability) and late (without the ability to differentiate) passages of adipose derived hMSCs, using high density lectin microarray, demonstrated that early passage cells show stronger binding to specific lectins for α2,6-linked Sia (74). Bone marrow-derived hMSCs and cartilage tissue-derived chondrocytes also showed this similar binding activity, but no binding activity is indicated between α2,6-linked Sia and its specific lectins in human dermal fibroblasts.…”
Section: Mesenchymal Stem Cell Sialylated N-glycansmentioning
confidence: 99%